A Brief Perspective on the Existence of Indonesian Domestic Worker - M Dian Hikmawan; Gilang Ramadhan (Universitas Sultan Ageng Tirtayasa, 2022)
This study tries to elaborate on the dynamics that are happening to domestic workers (PRT) in the Indonesia. Very basic issues for female domestic workers include sexual violence, social welfare and child labor. The most serious is the work of underage girls, which makes research very important to do. By using a qualitative method with a political ethnographic approach. This research is expected to map the dynamics and provide a comprehensive picture of what challenges can be used as policies for Indonesian public discourse especially in Banten province in order to overcome these problems.